Implementation of Project Based Learning in Improving Early Childhood Interpersonal Intelligence - Puspitasari, Tri Endah; Robingatin, Robingatin; Muadin, Akhmad (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research study investigates the implementation of Project Based Learning (PBL) to enhance early childhood interpersonal intelligence. The study explores the steps involved in planning PBL and presents specific strategies for its implementation in early childhood settings. This study used a qualitative approach with data collection techniques in the form of semi-structured interviews, non-participant observation, and documentation. Data analysis used Milles, Huberman, and Saldana's interactive data analysis, namely: data condensation, data display, and conclusion. The research findings show that the implementation of PBL has a positive impact on students' interpersonal intelligence by promoting interaction, collaboration, and problem-solving skills. Strategies such as the division of diverse groups, assigning different roles, encouraging group discussions, providing peer feedback, and facilitating reflection, and evaluation were found to be effective in fostering interpersonal skills. Evaluation of PBL implementation involved formative and summative assessments, which allowed observation of student participation, feedback on interpersonal skills, assessment of project outcomes, and collecting feedback from students, parents, and teachers. The comprehensive evaluation process supports the effectiveness of PBL in improving early childhood interpersonal intelligence. The implications of this study highlight the importance of incorporating established educational theories and research findings into PBL planning, strengthening the theoretical foundation, and providing evidence-based support for the effectiveness of PBL in fostering early childhood interpersonal intelligence. The findings contribute to the field of early childhood education by providing practical guidance for educators who want to improve students' interpersonal skills through a project-based learning approach.